The Relationship Between ARV Therapy Adherence And Clinical Outcomes in HIV Patients at Dr Moewardi Hospital - Putri Eka Prasetya; Niken Luthfiyanti; Vivin Marwiyati Rohmana; Angelina da Costa Fernandes (Duta Pharma Journal, 2026)
Background: Human immunodeficiency virus (HIV) remains a major global public health problem with the number of people living with HIV continuing to increase, including in Indonesia. Antiretroviral therapy (ART) is the main treatment to suppress viral replication and improve immune function, however its success is highly dependent on patient adherence. Objective: This study aimed to determine the level of adherence to ART, evaluate clinical outcomes and analyze the relationship between ART adherence and clinical outcomes among HIV patients at Dr. Moewardi Hospital. Methods: This study employed a quantitative analytical design with a cross-sectional approach. A total of 83 patients (n=83) undergoing ART were included in this study. Data were collected using the Morisky Medication Adherence Scale (MMAS-8) and medical records. Data analysis was performed using univariate and bivariate methods. Results: The majority of patients demonstrated high adherence to ART (60.2%), followed by moderate adherence (34.9%) and low adherence (4.8%). Most patients achieved favorable clinical outcome with 89.2% having undetectable viral load and 10.8% having detectable viral load. CD4 levels were categorized as good (51.8%), very good (33.7%) and poor (14.5%). Bivariate analysis showed a significant relationship between ARV adherence and CD4 outcomes (p = 0.007) as well as viral load outcomes (p < 0.000). Conclusion: There is a significant relationship between ART adherence and clinical outcomes in HIV patients. Higher adherence is associated with improved CD4 levels and viral load suppression.